Cardiopulmonary function and scoliosis severity in idiopathic scoliosis children - Seokwon Huh; Lucy Yougmin Eun; Nam Kyun Kim; Jo Won Jung; Jae Young Choi; Hak Sun Kim (Korean Pediatric Society, 2015)
PurposeIdiopathic scoliosis is a structural lateral curvature of the spine of unknown etiology. The relationship between degree of spine curvature and cardiopulmonary function has not yet been investigated. The purpose of this study was to determine the association between scoliosis and cardiopulmonary characteristics.MethodsNinety children who underwent preoperative pulmonary or cardiac evaluation at a single spine institution over 41 months were included. They were divided into the thoracic-dominant scoliosis (group A, n=78) and lumbar-dominant scoliosis (group B, n=12) groups. Scoliosis severity was evaluated using the Cobb method. In each group, relationships between Cobb angles and cardiopulmonary markers such as forced vital capacity (FVC), forced expiratory volume in one second (FEV1), FEV1/FVC, left ventricular ejection fraction, pulmonary artery flow velocity, and tissue Doppler velocities (E/E', E'/A') were analyzed by correlation analysis linear regression.ResultsIn group A, 72 patients (92.3%) underwent pulmonary function tests (PFTs), and 41 (52.6%) underwent echocardiography. In group B, 9 patients (75.0%) underwent PFT and 8 (66.7%) underwent echocardiography. Cobb angles showed a significant negative correlation with FVC and FEV1 in group A (both P<0.05), but no such correlation in group B, and a significant negative correlation with mitral E/A ratio (P<0.05) and tissue Doppler E'/A' (P<0.05) in group A, with a positive correlation with mitral E/A ratio (P<0.05) in group B.ConclusionPulmonary and cardiac function was significantly correlated with the degree of scoliosis in patients with thoracic-dominant scoliosis. Myocardial diastolic function might be impaired in patients with the most severe scoliosis.